Implementation Of Complete Systematic Land Registration (PTSL) In The Village Of Tanjungharjo, Ngaringan Sub-District, Grobogan District - Edo Iranda Novatama; Umar Ma’ruf (Jurnal Akta, 2019)
The purpose of this study was to: 1) To determine and analyze Systematic implementation of the Complete Systematic Land Registration in Village of Ngaringan, Tanjungharjo Subdistrict, Grobogan District 2) To identify and analyze the obstacles faced in the Complete Systematic Land Registration in Village of Ngaringan, Tanjungharjo Subdistrict, Grobogan District. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by sociological methods.Based on the results of data analysis concluded that: 1) Implementation of PTSL by adjudication teams dominate in their respective fields in their duties, their dexterity of team officials adjudication PTSL in performing their duties which is always ready to be in place basecamp / office Adjudication Team in terms of running activities, the cooperation with the village as well as their facilities and infrastructure such as the computerized system so that it becomes a factor that support the implementation of land registration through PTSL program. Rural communities in the program areas PTSL responded well and was very happy to participate as the program participants as evidenced by the demand from the public to register as a participant PTSL program that exceeds that of the set target. 2) Obstacles that occur in the field, among others, lack of knowledge of the importance of data collection for the certificate issuance process, so people tend to underestimate completeness impressed application file such as ID cards and SPPT (Income Tax Payable). In addition proof of ownership of the land acquired is minimal, so that the necessary statements and testimony. Then the location of Block SPPT on the rights object not fit image map Ricikan Block PBB Layout object existing rights in Block SPPT incompatible with image map Ricikan Block PBB, making it difficult for the task force juridical data collectors in determining the location of the object that right.Keywords: PTSL; Implementation; Obstacles.